PEMANFAATAN REFERENCE MANAGEMENT SOFTWARE (RMS) UNTUK PENYUSUNAN KARYA ILMIAH DI PERGURUAN TINGGI - mufid mufid (Pustakaloka, 2014)
Reference management software (RMS) is useful application for  researchers,  lecturers  and  students  helping  them  to  compose scientifc paper. This software has  fuctioned to search online scientifc information, to save search results, and to write bibliography, includes making  citation  and  references  automatically,  to  facilitate  to  share references  with  other  users  and  to  sincron  references  web  based  on desktop or mobile phone.This  article  tries  to  introduce  RMS. Using  RMS,  error  on  writing citation  and  references  can  be  avoided,  publishing  of  scientifc works would be increased and more qualifed.